Analysis of Oxygen Supply and Demand amid the Coronavirus Disease 2019 (COVID-19) Pandemic in Thailand, 2021 - Thamarangsi, Thaksaphon; Phonsuk, Payao; Suphanchaimat, Rapeepong; Rajatanavin, Nattadhanai (OSIR Journal, 2021)
The need for medical oxygen in Thailand tends to be increasing due to rising coronavirus disease 2019 (COVID-19) cases. An analysis of oxygen supply and demand can provide a useful insight into the demand for oxygen therapy during the pandemic. To overcome the oxygen supply crisis, the government needs to address the shortage of related equipment, such as oxygen cylinders, generators and concentrators, which are mostly used for home and community isolations and also in field hospitals. We recommend that the government should dramatically increase the capacity for oxygen production as well as the production of related equipment. Furthermore, mechanisms to ensure adequate and equitable distribution of oxygen therapy should be in place. A promotion of domestic research and development to increase the capacity of oxygen production and ensure equitable oxygen distribution is urgently needed. Keywords:  oxygen supply, demand, COVID-19, Thailand